FRI0193 SC vs IV abatacept in RA: post-hoc efficacy analysis of long-term acquire (SC) data with aim (IV) data. (23rd January 2014) - Genovese, M.; Pacheco Tena, C.; Covarrubias Cobos, A.; Leon, G.; Mysler, E.F.; Keiserman, M.; Valente, R.; Nash, P.; Simon Campos, J.A.; Box, J.; Legerton, C.W.; Nasonov, E.; et al.
Abstract : Background: ACQUIRE was a Ph IIIb study demonstrating comparability of SC and IV abatacept (ABA) over a 6-mth DB period. At 6 mths, all patients (pts) entered an open-label (OL) period in which they received SC ABA. AIM was a Ph III 12-mth, DB, placebo-controlled study of IV ABA, also with an OL extension. Pts in both trials had moderate-to-severe RA, inadequate response to MTX and similar BL demographics and disease activity. Objectives: To provide a long-term (LT) comparison of SC and IV ABA, we performed a post-hoc efficacy analysis of LT data from the OL periods of ACQUIRE and AIM. Methods: In ACQUIRE, pts received 125 mg SC ABA weekly (after 10 mg/kg IV load on Day 1) +MTX. In AIM, pts received ∼10 mg/kg IV ABA every 4 weeks (after loading doses on Days 1, 15 & 29) +MTX; only pts who received ABA in DB and OL periods were included in this analysis. LT analysis began at Day 253 for ACQUIRE; Day 225 was selected as a comparison starting point for AIM. The most recent LT data lock for ACQUIRE (Day 897) was then used as the comparison end date for AIM as well. At the time of analysis, however, not all ACQUIRE pts had reached this later time point. As-observed data were used to assess both response to treatment (ACR 20, 50 and 70) and disease status (DAS28[CRP], SDAI and CDAI). No safety analyses were performed on this subset as larger pooled safety analyses are presented elsewhere. Results: In the OL period of ACQUIRE, 1372 pts received SC ABA compared with 378 pts who received IV ABA in AIM. ACR 20, 50 and 70 rates, and DAS remission rates were sustained from Days 253/225 through Day 897 for ACQUIRE/AIM, respectively (Table ). SDAI and CDAI remission rates at Day 253 (13.3%; 179/1341 and 15.6%; 211/1349) were maintained up to Day 897 (20.2%; 123/608 and 22.1%; 143/646) in ACQUIRE; in AIM, corresponding rates at Day 225 (9.9%; 36/365 and 12.2%; 45/369) were similarly maintained up to Day 897 (15.0%; 45/300 and 16.7%; 52/311). Conclusions: SC abatacept provided similar efficacy to IV abatacept when compared across these 2 trials; overall, efficacy achieved in the short term was maintained in the LT. Disclosure of Interest: M. Genovese Consultant for: Bristol-Myers Squibb, C. Pacheco Tena: None Declared, A. Covarrubias Cobos Grant/Research support from: Bristol-Myers Squibb, G. Leon: None Declared, E. Mysler Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, M. Keiserman Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, R. Valente Grant/Research support from: Pfizer, UCB, BMS, Roche, Takeda, and Lilly, P. Nash Grant/Research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, J. Simon Campos Speakers Bureau: Bristol-Myers Squibb, J. Box Consultant for: Bristol-Myers Squibb, Speakers Bureau: Bristol-Myers Squibb, C. Legerton III: None Declared, E. Nasonov Speakers Bureau: Roche; Bristol-Myers Squibb Company; Abbott Laboratories; Merck Sharp & Dohme Corp; UCB Pharma, Inc, P. Durez Speakers Bureau: Bristol-Myers Squibb, I. Delaet Employee of: Bristol-Myers Squibb, A. Elegbe Employee of: Bristol-Myers Squibb, R. Alten Grant/Research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers Bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis